2016
DOI: 10.1080/10286020.2016.1251908
|View full text |Cite
|
Sign up to set email alerts
|

Neural anti-inflammatory sesquiterpenoids from the endophytic fungus Trichoderma sp. Xy24

Abstract: Three new sesquiterpenoids trichoacorenols B-C and cyclonerodiol B (1-3), along with three known ones (4-6), were isolated from the mangrove plant endophytic fungus Trichoderma sp. Xy24 using various column chromatography techniques. The structures of these compounds were determined on the basis of extensive spectroscopic data analyses. Compounds 1, 2, 4, and 5 were four acorane sesquiterpenes, 3 and 6 were two monocyclic sesquiterpenediols. Compounds 3 and 5 exhibited significant neural anti-inflammatory acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…Mosher's method (Cao et al, 2014) was tried to determine the absolute configuration of C-7 but failed. Fortunately, a literature survey revealed that the coisolated cyclonerane-type compounds (4-9) and many other similar natural compounds have been reported the same absolute configurations as 2S,3R,6R,7R (Hanson et al, 1975;Kasitu et al, 1992;Li et al, 2007;Wu et al, 2012;Xie et al, 2013;Zhang et al, 2017;Fang et al, 2018;Song et al, 2018). Therefore, based on the biogenetic considerations, compound 3 was proposed to have the same absolute configuration (2S,3R,6R,7R) as the co-isolated compound 9, which was also supported by their similar OR between 3 ([α] 22 D -29.9 (c 1.00, CHCl 3 )) and 9 ([α] 22 D -26.6 (c 1.00, CHCl 3 ); lit.…”
Section: Chemical Identification Of the Isolated Compoundsmentioning
confidence: 99%
“…Mosher's method (Cao et al, 2014) was tried to determine the absolute configuration of C-7 but failed. Fortunately, a literature survey revealed that the coisolated cyclonerane-type compounds (4-9) and many other similar natural compounds have been reported the same absolute configurations as 2S,3R,6R,7R (Hanson et al, 1975;Kasitu et al, 1992;Li et al, 2007;Wu et al, 2012;Xie et al, 2013;Zhang et al, 2017;Fang et al, 2018;Song et al, 2018). Therefore, based on the biogenetic considerations, compound 3 was proposed to have the same absolute configuration (2S,3R,6R,7R) as the co-isolated compound 9, which was also supported by their similar OR between 3 ([α] 22 D -29.9 (c 1.00, CHCl 3 )) and 9 ([α] 22 D -26.6 (c 1.00, CHCl 3 ); lit.…”
Section: Chemical Identification Of the Isolated Compoundsmentioning
confidence: 99%
“…1α-isopropyl-4α,8-dimethylspiro dec-8-ene-3β,7αdiol (26) Trichoderma sp. Xy24 Xylocarpus granatum [15] 10.…”
Section: -Epichaetomugilin I (57)mentioning
confidence: 99%
“…They are characterized by a highly substituted per hydro-isoindolone moiety to which a macrocyclic ring like a carbocycle, a lactone, or a cyclic carbonate is fused [54]. Four AI cytochalasan derivatives [cytochalasin J (12) and H (13), yamchaetoglobosin A (14), and phomopchalasin C (15)] from endophytic fungal sources were reported (▶ Fig. 2).…”
Section: Ai Cytochalasansmentioning
confidence: 99%
See 1 more Smart Citation
“…In another investigation, three new sesquiterpenoids, trichoacorenols B-C and cyclonerodiol B, along with three known ones, isolated from the mangrove plant endophytic fungus Trichoderma sp. Xy24 were reported to exhibit varying degree of anti-inflammatory activity with cyclonerodiol B (153) and (1R,2R,4S,5R,7S)-4-isopropyl-1,8-dimethylspiro [4.5]dec-8-ene-2,7-diol (154) being more potent than curcumin, used as positive control [125].…”
Section: Anti-inflammatory Metabolites Produced By Endophytic Fungi Fmentioning
confidence: 99%